Epidemiological analysis of alcoholic liver disease in the state of Sergipe (Research, Society and Development, 2022)
Abstract Introduction: Excessive alcohol consumption is associated with a series of liver manifestations, affecting human health worldwide. Alcoholic liver disease (ALD) represents a spectrum of liver damage resulting from chronic alcohol consumption, ranging from hepatic steatosis to more advanced forms, including alcoholic hepatitis, cirrhosis, and chronic liver failure. Objective: To describe the epidemiology of cases of hospitalizations and deaths of Alcoholic Liver Disease in the state of Sergipe from 2010 to 2020, according to health regions, sex and age group. Methodology: Refers to a cross-sectional, descriptive and retrospective epidemiological study. The unit of analysis of this study was the DHA morbidity and mortality data (ICD10-K70) from January 2010 to December 2020, in the state of Sergipe, obtained through DATASUS. Results: In this period, 1060 hospitalizations were reported and 320 of these cases evolved to death, as a result of ALD in the state of Sergipe. The incidence of hospitalizations and deaths was higher in men. The risk of hospitalization and death from ALD was higher in the age group between 50-59 years. The health region of Sergipe, with the highest incidence of hospitalizations and deaths due to ALD, was Aracaju. Conclusions: Because ALD is a condition associated with several complications, being underdiagnosed or diagnosed in advanced stages with irreversible liver damage, it is mandatory to create public policies aimed at preventing the consumption of alcoholic beverages.